The Length Fatigue Levels of Time Undergoing Hemodialysis In Chronic Kidney Disease Patients - Shobirun; Umi Margi Rahayu; Fatikhah Amara Sari; S. Eko Ch Purnomo (Jendela Nursing Journal (JNJ), 2026)
Background: Chronic Kidney Disease (CKD) is a progressive condition that often requires long-term hemodialysis (HD) to sustain life. However, HD is associated with fatigue, which affects approximately 60–97% of patients and significantly impacts their quality of life. Purpose: This study aimed to determine the correlation between the length of time undergoing hemodialysis and fatigue levels in CKD patients. Methods: A cross-sectional study was conducted at the Hypertension Kidney Clinic Lestari Semarang, involving 68 CKD patients undergoing HD. Fatigue levels were measured using the Fatigue Assessment Scale (FAS). Data were analyzed using the Gamma correlation test. Results: The results showed a statistically significant positive correlation between the length of time undergoing hemodialysis and fatigue levels (p = 0.001; correlation coefficient = 0.798), indicating that longer treatment duration is associated with higher fatigue. Conclusion: These findings suggest that the longer a patient undergoes hemodialysis, the more severe the fatigue experienced. It is recommended that healthcare providers implement targeted educational and rehabilitative interventions to reduce fatigue in long-term HD patients and improve their quality of life.